Adapting the Wizard of Oz musical adaptations from Baum to MGM and beyond - Birkett, Danielle 1989-; McHugh, Dominic ca. 20./21. Jh (Oxford University Press, 2018)
This volume examines 'The Wizard of Oz' and its surrounding culture, centering on three areas of study: early adaptations of Baum's novels, insights into the MGM film, and the legacy of 'The Wizard of Oz' on the popular stage. Although the articles will devote some attention to the genesis of the musical and the biographical profiles of the creative team, the text will prioritize critical and analytical readings
Includes bibliographical references and index
Keywords: Baum, L. Frank / (Lyman Frank) / 1856-1919 / Wizard of Oz; Baum, L. Frank -- 1856-1919 -- The wonderful wizard of Oz; Wizard of Oz (Motion picture : 1939); The wizard of Oz; Geschichte; Oz (Imaginary place) / Songs and music / History and criticism; Musicals / United States / History and criticism; Musical films / United States / History and criticism; Motion picture music / United States / History and criticism; Musik; Film; Musical; Rezeption; USA; Aufsatzsammlung